Bölgesel Kalkınma Ajansları Ve Yönetişim: Doğu Marmara Kalkınma Ajansı Uygulaması Olarak Düzce Turizm Strateji Ve Eylem Planı Örneği - Yılmaz, Serkan (Fen Bilimleri Enstitüsü, 2016)
Dünyayı küçük bir köy haline getiren küreselleşme, geleneksel yönetim modelleri yerine yenilikçi yaklaşımların geliştirilmesi ihtiyacını doğurmuştur. Yönetişim kavramı, klasik yönetim biçimlerinin zaafları neticesinde doğmuş gibi görünmekle birlikte, genel olarak gücün kendisinden ziyade, nasıl kullanılacağıyla ilgilenmektedir. Bu bağlamda yönetişim; çeşitli işbirliği modellerini içinde barındıran, toplumun her kesiminden katılımı esas alan ve taraflar arasında etkileşimi yüksek tutan bir çoklu-karar verme sürecidir. İyi yönetişim kavramı ise, Dünya genelinde ekonomik kalkınmaya önem veren birçok uluslararası donör kurum tarafından kullanılan bir terim olup, hesap verebilirlik, hukukun üstünlüğü, katılım, şeffaflık ve uyum gibi çeşitli kriterlerle yönetişimin iyi yapılıp yapılmadığına yönelik bir değerlendirmedir. Bölgesel kalkınma ajansları, özellikle İkinci Dünya Savaşı’nın olumsuz etkileri sonrasında yaşanan yeniden yapılanma faaliyetleri sonucu ortaya çıkmış olup, giderek daha da belirginleşmeye başlayan bölgelerarası farklılıkları gidermeye yönelik politikalar üretme ve uygulama araçlarından biridir. 50 yılı aşkın bir süredir etkin bir biçimde birçok ülkede faaliyet gösteren bölgesel kalkınma ajansları; genellikle kamu yönetimi tarafından finanse edilen, bölgesel ekonomik gelişmeyi özendirmek üzere merkezi ve yerel hükümetin arasında bir düzeyde oluşturulan ve modern yönetişim unsurları çerçevesinde çalışan kurumsal yapılardır. Türkiye’de bölgesel kalkınma ajansı kurma çabaları, 2000’li yılların başında Avrupa Birliği’ne üyelik sürecinin hızlanmasına paralel olarak ivme kazanmıştır. 2002 yılında İstatistiki Bölge Birimi Sınıflandırmasının (İBBS) kabul edilmesiyle başlayan süreç, 2003 yılında Avrupa Birliği’ne Katılım Ortaklığı Belgesinde ve Ön Ulusal Kalkınma Planında kalkınma ajansların kurulmasına yönelik taahhütler verilmesiyle devam etmiştir. 2006 yılında 5449 sayılı Kalkınma Ajanslarının Kuruluşu, Koordinasyonu ve Görevleri Hakkında Kanun çıkarılmış ve bunu takip eden 3 yıl içerisinde İBBS-2 düzey bölgelerinde 26 adet bölgesel kalkınma ajansı kurulmuştur. Bu çalışma ile ülkemizde merkezi yönetim ile yerel yönetim arasındaki bir ölçekte örgütlenen, karar vericiler ile toplumun her kesiminden temsilciyi içinde barındıran bir yapıda kurgulanan, bölgesinin ekonomik kalkınmasına yönelik faaliyetlerde bulunan bölgesel kalkınma ajanslarının uygulamalarının; çeşitli iyi yönetişim unsurları bakımından hangi düzeyde olduğunun araştırılması amacıyla yapılmıştır. Bu çalışma, Düzce Turizm Strateji ve Eylem Planı örneği üzerinden kalkınma ajanslarının sunmuş olduğu destek faaliyetlerinin; iyi yönetişim kriterleri açısından uygulanabilirliğine yönelik detaylı bilgi edinilmesini sağlayacaktır.

Starting by the end of the 20th century, the changes which are mostly caused by technological developments, transformed the world to a little village. Globalization which can be explained as free circulation of capital, knowledge and humanity in the world; bring out the need of change in traditional organization and management methods. Governance concept seems like to be emerged by the weakness of traditional management methods, and main challenge about is how to use power more than power itself. Governance fundamentally based on mutual responsibility among ruler and community being ruled, and by increasing communication and interaction tries to include all fractions of the community and ensure the agreement. On this context governance is a multi-decision making process which includes many cooperation models, encourages the participation of all fractions of the community and maintains interaction between them. Good governance concept mainly used by donor institutions like United Nations, European Union, OECD and IMF, and is an evaluation whether governance is good or not in terms of accountability, rule of law, participation, transparency and cohesion principles. In meaning of socio-economic issues, regional development disparities reached to an extent which cannot be ignored, and can be faced every kind of administrative level like among countries in the world, regions in a country, cities in a region, neighbourhoods in a city. When globalization process investigated, it can be seen that a localization movement take place parallel to globalization. In meaning of localization, main aim is to carry out services effectively by local governors via decentralization of the power. Regional development agencies, especially come forward after the Second World War in reconstruction activities and is a good instrument for producing policy for reducing the regional disparities. Regional development agencies is actively taking place in many countries more the 50 years and usually financed by the public sector and based on governance principles. Efforts of establish regional development agencies in Turkey starts by the 2000’s because of the process of being a member of European Union. Turkey has made some legitimate arrangements to fulfil duties to become a member to European Union and first structural arrangement is to adapt the regional system of Europe. In 2002, Turkey defined its own NUTS classification which is called IBBS to establish regional development agencies. In 2006, Turkey brought out law no: 5449 and legal basis for regional bodies has been founded. Between 2006 and 2009, 26 regional development agency has been built in Turkey. One of the 26 agencies established in Turkey is East Marmara Development Agency (MARKA) and which includes Kocaeli, Sakarya, Düzce, Bolu and Yalova provinces. MARKA founded at 25.07.2009 and describe itself as a “typical public institution, vested with a special legal entity, prepares regional development strategies with providing coordination and cooperation between public sector, private sector and non-governmental organizations in its comprising five provinces, conducts works for the purpose of proper and effective use of resources and potentials of the region to accelerate the development of East Marmara and to strengthen its situation in global competitiveness”. MARKA’s mission is to determine the strategies for utilizing of the social and economic resources that will contribute to the further and to ensure the coordination of all stakeholders and participation of its employees for the purpose of sustainable development in East Marmara. The aim of the study is to investigate good governance principles in terms of practicality of the regional development agencies’ support activities which are formed in a level between central and local governments, and which includes decision makers and all kinds of representatives of community. Based on these perceptions explained above, main assumption of the study is defined as “Regional development agencies which are formed in a structure never observed before in Turkey, directs regional development by producing plans and also allows good governance practice”. The truthfulness of main assumption of the study has been done by investigation of these question given below; i. How gorvernance phenomenon developed as a innovative concept in the world and Turkey and in which principles of governance can be measured whether it is good or not? ii. How regional development agencies are historically developed, formed, financed, and what are the main actors, aims, activities and practice in the world and Turkey? iii. What governance principles looked for the projects supported by regional development agencies? How regional development agencies measure and oversee good governance principles? This study will help us get more information about the practicality of regional development agencies’ support activities in terms of good governance principles and in case of Düzce Tourism Strategy and Action Plan. Study starts with the second chapter which investigates governance concept. In second chapter; first, an evaluation of historical development and actors of governance at world and Turkey has been made, and then critics on governance phenomenon and good governance principles analyzed in terms of Turkey. Mainly on this chapter, govern tradition of uniter state and governance method based on multi-actor decision making have been compared. In following chapter; definitions, general structures, financial sources, main aims and activities, participating actors of regional development agencies has been analyzed and regional development agency establishment experience in Turkey has been evaluated over the chapter’s case study East Marmara Development Agency (MARKA) In fourth chapter; an assessment has been made about the good governance principles for the implementations of regional development agencies via Düzce Tourism Strategy and Action Plan case study which was supported by MARKA. Finally the study comes to end with a results and suggestions chapter.
Regional Development Agencies And Governance: East Marmara Regional Development Agency And Duzce Tourism Strategy And Action Plan Case
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2016
Keywords: Bölgesel Kalkınma Ajansları; Doğu Marmara Kalkınma Ajansı; Marka; Yönetişim; İyi Yönetişim; Düzce; Turizm Strateji Ve Eylem Planı; Regional Development Agencies; East Marmara Regional Development Agency; Marka; Governance; Good Governance; Düzce; Tourism Strategy And Action Plan